2013
DOI: 10.1002/rcm.6711
|View full text |Cite
|
Sign up to set email alerts
|

Deiodination of iodinated aromatic compounds with electrospray ionization mass spectrometry

Abstract: Care should be taken when using formic acid as a mobile phase additive in LC/MS analyses of iodinated aromatic compounds, since the interpretation of the mass spectra might be influenced by potential dehalogenation reactions taking place in the ESI capillary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…No deiodinated species was observed for both iodixanol and iohexol within the conditions evaluated in this study. 17 …”
Section: Resultsmentioning
confidence: 99%
“…No deiodinated species was observed for both iodixanol and iohexol within the conditions evaluated in this study. 17 …”
Section: Resultsmentioning
confidence: 99%
“…The NL-peaks were also detected in standard solution. Hvattum et.al . investigated this behavior and found that formic acid induces deiodination in the ESI capillary of the MS instrument.…”
Section: Resultsmentioning
confidence: 99%
“…Hvattum et.al. 21 investigated this behavior and found that formic acid induces deiodination in the ESI capillary of the MS instrument. The same was observed for IOX-TP695-A and B, where (apart from the two TPs) a neutral loss of iodine from IOX shows a peak at 2.89 min which is the same retention time as IOX.…”
Section: )mentioning
confidence: 99%
“…Finally, dehalogenation of iodinated aromatic compounds when performing HPLC-ES-MS/MS measurement in both +ve and Àve modes has been reported by Hvattum et al 120 The iodinated aromatic compounds were analyzed on a YMC-Pack ODS AM column (150 Â 4.6 mm, 5 mm) using gradient elution from 100% water to 50% acetonitrile. In the rst 118 iodine speciation in human urine by RP HPLC-ICP-MS is described.…”
Section: Halogensmentioning
confidence: 98%
“…It was found that I was associated with alkaline proteins with RMM of 10, 20, 28, 40 and 110 kDa in the alkaline (pH 8.0-9.0) isoelectric point (pI) range. Finally, dehalogenation of iodinated aromatic compounds when performing HPLC-ES-MS/MS measurement in both +ve and Àve modes has been reported by Hvattum et al 120 The iodinated aromatic compounds were analyzed on a YMC-Pack ODS AM column (150 Â 4.6 mm, 5 mm) using gradient elution from 100% water to 50% acetonitrile. The effect of mobile phase additive on the deiodination reaction was evaluated by using formic acid, acetic acid, triuoroacetic acid, ammonium formate and ammonium acetate as modiers.…”
Section: Halogensmentioning
confidence: 98%